Ethnic discrimination in contacts with public authorities: A correspondence test among Swedish municipalities - Ali M. Ahmed; Mats Hammarstedt (Research Institute of Industrial Economics (IFN), 2019)
We present a field experiment conducted in order to explore the existence of ethnic discrimination in contact with public authorities. Two fictitious parents, one with a Swedish-sounding name and one with an Arabic-sounding name, sent email inquiries to all Swedish municipalities asking for information about preschool admission for their children. Results show that the parents were treated differently by the municipalities since the individual with the Swedish-sounding name received significantly more responses that answered the question in the inquiry than the individual with the Arabic-sounding name. Also, the individual with the Swedish-sounding name received more warm answers than the individual with the Arabic-sounding name in the sense that the answer from the municipality started with a personal salutation. We conclude that ethnic discrimination is prevalent in public sector contacts and that this discrimination has implications for the integration of immigrants and their children.
Keywords: J15; C93; H83; 330; Discrimination; Subtle discrimination; Authorities; Field experiment